A survey on features of allergic rhinitis in children. (May 2013) - Zicari, A.M.; Indinnimeo, L.; De Castro, G.; Incorvaia, C.; Frati, F.; Dell'Albani, I.; Puccinelli, P.; Scolari, M.; Duse, M.; ,
Abstract Objective: A number of epidemiologic studies evaluated the prevalence of allergic rhinitis (AR), but few data are available on its different clinical presentations. We addressed this survey to assess the features of AR in children and adolescents. Methods: Thirty-five centers in Italy included 2623 pediatric patients with rhinitis, of whom 2319 suffered from AR, while 304 had other kinds of rhinitis. For each patient a standardized questionnaire was filled in, including ARIA classification, the duration of symptoms, the allergen identified as clinically relevant, the co-morbidities, the kind of treatment, the response to treatment, the satisfaction with the treatment, and the feasibility of allergen immunotherapy (AIT). Results: Of the 2319 patients, 597 (25.7%) had mild intermittent, 701 (30.2%) mild persistent, 174 (7.5%) moderate–severe intermittent, and 773 (33.3%) moderate–severe persistent AR. The allergens most relevant were grass pollen and dust mites. The most frequently used drugs were oral antihistamines (83.1%) and topical corticosteroids (63.5%). The response to treatment was judged as excellent in 13.5%, good in 45.1%, fair in 30.8%, poor in 10%, and very bad in 0.6% of cases. The satisfaction with treatment was judged as very satisfactory in 15.2%, satisfactory in 61.8%, unsatisfactory in 22.4%, and very unsatisfactory in 0.5% of cases. AIT was considered indicated in 53.1% of patients with mild intermittent, 79.2% of moderate–severe intermittent, 72.6% of mild persistent, and 82.7% of moderate–severe persistent AR. Conclusions: The limitation of this study is that the population was not unselected and this prevents epidemiological significance. These results offer confirmation of the adequacy of ARIA guidelines in classifying patients with AR and of the association of severe phenotype with lack of success of drug treatment.